ANALYSIS OF STUDENTS MATHEMATICAL REPRESENTATION AND CONNECTION ON ANALYTICAL GEOMETRY SUBJECT - Muchamad Subali Noto; Wahyu Hartono; Dadan Sundawan (IKIP Siliwangi and I-MES, 2016)
The importance ability of mathematical representation and connection to owned by the student really help students in understanding the mathematical concepts in the form of pictures, symbols, and the written word. The use of mathematical representation and the correct connection by students will help students make mathematical ideas more concrete and can connect a concept to another concept, so that students can develop a view of mathematics as a whole integration. This research aims to describe and analyze the ability of representation and mathematical connection on the topics of analytical geometry. The research method was descriptive with the subject as much as 22 mathematics students. Data collected through tests and interviews. The results show that the average ability of representation is 46.00; the average mathematical connection ability is 36.77. This means both the abilities still belongs to low, particularly for the ability of mathematical connection.